Estudo de uma técnica para o tratamento de dead-times em operações de rastreamento de objetos por servovisão - Saqui, Diego (2014)
Visual servoing is a technique that uses computer vision to acquire visual information (by camera) and a control system with closed loop circuit to control robots. One typical application of visual servoing is tracking objects on conveyors in industrial environments. Visual servoing has the advantage of obtaining a large amount of information from the environment and greater flexibility in operations than other types of sensors. A disadvantage are the delays, known as dead-times or time-delays that can occur during the treatment of visual information in computer vision tasks or other tasks of the control system that need large processing capacity. The dead-times in visual servoing applied in industrial operations such as in the tracking of objects on conveyors are critical and can negatively affect production capacity in manufacturing environments. Some methodogies can be found in the literature for this problem and some of these methodologies are often based on the Kalman filter. In this work a technique was selected based on the formulation of the Kalman filter that already had a study on the prediction of future pose of objects with linear motion. This methodology has been studied in detail, tested and analyzed through simulations for other motions and some applications. Three types of experiments were generated: one for different types of motions and two others applied in different types of signals in the velocity control systems. The results from the motion of the object shown that the technique is able to estimate the future pose of objects with linear motion and smooth curves, but it is inefficient for drastic changes in motion. With respect to the signal to be filtered in the velocity control, the methodogy has been shown applicable (with motions conditions) only in the estimation of pose of the object after the occurrence of dead-times caused by computer vision and this information is subsequently used to calculate the future error of the object related to the robotic manipulator used to calculate the velocity of the robot. The trying to apply the methodogy directly on the error used to calculate the velocity to be applied to the robot did not produce good results. With the results the methodogy can be applied for object tracking with linear motion and smooth curves as in the case of objects transported by conveyors in industrial environments.